Plant immune systems as pests and diseases mitigation. Issue 1 (July 2021) - Purnomo, D
Abstract: The phenomenon of climate change, which is currently still in the form of a weather anomaly, has disrupted the agricultural system. Increasing temperatures and changing rain patterns have resulted in several disasters such as heatwaves, strong winds (typhoons), and floods. For plants, these conditions result in disruption of plant growth and response to herbivores and pathogens. Plants have a mechanism of resistance to pests and pathogens intrinsically and extrinsically through growth, special morphology, metabolism of certain compounds such as volatiles (becoming disliked by herbivores or inviting natural enemies), and secondary metabolites. Secondary metabolites protect plants from pests (herbivores) and infection by disease microbes through mechanisms at the structural and metabolic levels. The level of the herbivore structure cannot penetrate, preventing mechanical damage. Secondary metabolites by inducing the synthesis of antibiotics derived from phenolics and terpenoids (phytoalexin). Antibiotics affect herbivores by suppressing growth, development, reproduction, to death. Secondary metabolites are typical of a plant as anti-insect, anti-fungal, anti-bacterial, and anti-viral compounds. Engineering to increase plant immunity against pests and pathogens by increasing secondary metabolites, cultivation, and genetic potential is developed. This program is not only related to environmentally friendly crop cultivation but also to anticipate climate change.